The Time Effect Of Extraction With Natural Dyes Morin Jackfruit Wood Powder By Using Some Variation of Solvent - Arwati, I Gusti Ayu; Wedhasari, Tyas (World Chemical Engineering Journal, 2016)
The aim of this study is to obtain a dye source which is can be degraded easily. Themajority of natural dyes extracted from plants is easily degraded dye. Plants that can be used as a coloring agent such as jackfruit wood (Artocorpusheterophyllus) taken from the morin containing a yellow dye. This study aims to find the best extraction time of morin from jackfruit sawdust using some solvent (Ethanol, Hexane and Acetone). The research was carried out in chemical laboratories in PT Sanova. From the research that has been done, found the best extraction time for 2hours with a yield of 8.36% morin.